Legal aspects of "White-label" banking in the European, Polish and German law - Michał Grabowski (Journal of Risk and Financial Management, 2021)
Offering "White-label" products and services is a well-developed business sector in the European market. At present, this market concept is also increasingly being applied to financial services, as part of a bank-FinTech cooperation. A question arises, however, as to the proper place for such models within the complex system of European financial law. This article reviews the "White-label" frameworks currently operating in the banking sector and the corresponding regulations of the European Union law, based on their application in German and Polish legal system. Purposive, grammatical, and comparative law methods were used to study the content of legal acts. As a result, the principles of two primary models of White-label banking were established. The first model is based on a bank acting only as an outsourcing service provider. In the second model, a bank also operates on the basis of a license it was granted. Both models have a common legal origin in European Union law, but local variations exist depending on the legal system of a given Member State.
Keywords: 330; bank in the box; banking as a service; FinTech; open banking; outsourcing of banking activities; PSD2; white-label banking